Modeling team performance from the perspective of politics and ethical leadership. Issue 5 (17th June 2019) - Lin, Chieh-Peng; Liu, Na-Ting; Chiu, Chou-Kang; Chen, Kuang-Jung; Lin, Ni-Chen
Abstract : Purpose: The purpose of this paper is to develop and test a model of team performance by applying social exchange and social capital perspectives in a single model setting. It hypothesizes that team performance is indirectly affected by politics through leader–member capitalization (LMC) and by ethical leadership through leader–member exchange (LMX). Meanwhile, team identification is hypothesized to moderate the relationships between politics and LMC and between ethical leadership and LMX. Design/methodology/approach: The hypotheses of this study were empirically tested using a survey of work teams from the banking and insurance industry in Taipei, Taiwan. Findings: The relationship between team performance and ethical leadership is fully mediated by LMX, while the indirect relationship between team performance and politics is mediated via both LMC and LMX. Team identification positively moderates the relationship between ethical leadership and LMX. Originality/value: This study is one of the few to examine the mediating roles of LMC and LMX simultaneously in team performance development. This study provides several key findings that complement the existing literature by evaluating fresh associations among LMC, LMX and their determinants and moderator.